Effect of Specimen Size on the Tensile Strength Behavior of the Plastic Waste Fiber Reinforced Soil – Lime – Rice Husk Ash Mixtures - Agus Setyo Muntohar (Civil Engineering Dimension, 2011)
Abstract: Improvement of tensile strength in fiber reinforced soil is an important research topic. A study has been undertaken to investigate the strength of stabilized clay-soil reinforced with randomly distributed discrete plastic waste fibers by carrying out split tensile strength test. In this study, the clay soil was stabilized with lime and rice husk ash mixtures. The main purpose of this research is to investigate the effect of specimen size to the tensile strength behavior. Testing procedure was formulated using extended ASTM C496 standard. The laboratory investigation results showed that split-tensile strength of reinforced specimens increased with increase in size. The limitations of the dataset indicate that specimen size of 70 mm in diameter is the threshold to produce reasonable representative strengths.